2004
DOI: 10.1037/0022-006x.72.6.1114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Forgiveness Therapy on Anger, Mood, and Vulnerability to Substance Use Among Inpatient Substance-Dependent Clients.

Abstract: Anger and related emotions have been identified as triggers in substance use. Forgiveness therapy (FT) targets anger, anxiety, and depression as foci of treatment. Fourteen patients with substance dependence from a local residential treatment facility were randomly assigned to and completed either 12 approximately twice-weekly sessions of individual FT or 12 approximately twice-weekly sessions of an alternative individual treatment based on routine drug and alcohol therapy topics. Participants who completed FT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
116
2
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(136 citation statements)
references
References 38 publications
8
116
2
3
Order By: Relevance
“…Three research groups obtained significant reductions in depression scores following forgiveness interventions with depressed clinical samples (Freedman & Enright, 1996;Lin, Mack, Enright, Krahn, & Baskin, 2004;Reed & Enright, 2006).…”
Section: Forgivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Three research groups obtained significant reductions in depression scores following forgiveness interventions with depressed clinical samples (Freedman & Enright, 1996;Lin, Mack, Enright, Krahn, & Baskin, 2004;Reed & Enright, 2006).…”
Section: Forgivenessmentioning
confidence: 99%
“…Interpersonal-forgiveness requires abandoning negative judgments and associated negative affect associated with the wrongdoer and giving up any right to retribution by not seeking revenge or holding grudges. In these definitions, self-forgiveness is intropunitive in orientation whereas other forgiveness is extrapunitive.Self-and other-forgiveness are associated with better mental health and well-being in general and student population samples (e.g., Maltby, Macaskill, & Day, 2001;Macaskill, 2012).Three research groups obtained significant reductions in depression scores following forgiveness interventions with depressed clinical samples (Freedman & Enright, 1996;Lin, Mack, Enright, Krahn, & Baskin, 2004;Reed & Enright, 2006). …”
mentioning
confidence: 99%
“…Furthermore, there is now some evidence indicating that positive interventions may not only be effective for reducing clinical symptoms in unselected populations, but they may be effective for reducing symptoms in clinical groups. In an inpatient sample of individuals with substance misuse problems, Lin et al (2004) found that forgiveness therapy was effective for reducing symptoms of anger, depression and anxiety.…”
Section: Symptoms Of Psychological Disordermentioning
confidence: 99%
“…Problem substance users also have higher levels of anger than non-problem substance users (7), and it has been suggested that this may be a defence against the shame associated with substance misuse (8). Both anger and resentment have in turn been found to be negatively related to forgiveness (9,10).…”
Section: Introductionmentioning
confidence: 99%